Fügen höchstfester Stahlgüten in Leichtbaustrukturen mittels selbststanzendem Widerstandselementschweißen auf konventionellen Widerstandspunktschweißanlagen - Günter, Heinrich; Meschut, Gerson (Tagungsband zum 8. Fügetechnischen Gemeinschaftskolloquium)

Konstruktive Gestaltung geklebter FVK-Mischverbindungen unter Berücksichtigung von Randeffekten - Göddecke, Johannes; Meschut, Gerson (20. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Model-driven development of condition monitoring software - Pasic, Faruk (Proceedings of the 21st ACM/IEEE International Conference on Model Driven Engineering Languages and Systems: Companion Proceedings)

Experimental characterization and numerical lifetime prediction of adhesively bonded joints under multiaxial fatigue loading - Çavdar, Serkan; Meschut, Gerson; Kroll, Ulrich; Matzenmiller, Anton (6th World Congress on Adhesion and Related Phenomena/ 41st Annual Meeting of The Adhesion Society)

A novel approach to enhance ACL injury prevention programs. - Gokeler, A; Seil, R; Kerkhoffs, G; Verhagen, E (J Exp Orthop)

Cross-education does not accelerate the rehabilitation of neuromuscular functions after ACL reconstruction: a randomized controlled clinical trial. - Zult, T; Gokeler, A; Raay JJAM, van; Brouwer, RW; Zijdewind, I; Farthing, JP; Hortobágyi, T (Eur J Appl Physiol)

Angle-specific analysis of isokinetic quadriceps and hamstring torques and ratios in patients after ACL-reconstruction. - Baumgart, C; Welling, W; Hoppe, MW; Freiwald, J; Gokeler, A (BMC Sports Sci Med Rehabil)

Transfer of improved movement technique after receiving verbal external focus and video instruction. - Benjaminse, A; Welling, W; Otten, B; Gokeler, A (Knee Surg Sports Traumatol Arthrosc)

The effect of load on Achilles tendon structure in novice runners. - Heyward, OW; Rabello, LM; van der Woude, L; van den Akker-Scheek, I; Gokeler, A; van der Worp, H; Zwerver, J (J Sci Med Sport)

Let us rethink research for ACL injuries: a call for a more complex scientific approach. - Gokeler, A; Verhagen, E; Hirschmann, MT (Knee Surg Sports Traumatol Arthrosc)

The Relationship between Sensory Responses to Ankle Joint Loading and Corticomotor Excitability - Needle, AR; Baumeister, Jochen; Farquahr, WB; Greaney, JL; Higginson, JL; Kaminski, TW; Swanik, CB (Int J Neuroscience)

Low rates of patients meeting return to sport criteria 9 months after anterior cruciate ligament reconstruction: a prospective longitudinal study - Welling, W; Benjaminse, A; Seil, R; Lemmink, K; Zaffagnini, S; Gokeler, A (Knee Surg Sports Traumatol Arthrosc)

Nonoperative treatment of muscle injuries - recommendations from the GOTS expert meeting - Hotfiel, T; Seil, R; Bily, W; Bloch, W; Gokeler, A; Krifter, RM; Mayer, F; Ueblacker, P; Weisskopf, L; Engelhardt, M (J Exp Orthop)

Altered movement during single leg hop test after ACL reconstruction: implications to incorporate 2-D video movement analysis for hop test - Welling, W; Benjaminse, A; Seil, R; Lemmink, K; Gokeler, A (Knee Surg Sports Traumatol Arthrosc)

Explainable Static Analysis - Bodden, Eric; Nguyen Quang Do, Lisa (Software Engineering und Software Management 2018, Fachtagung des GI-Fachbereichs Softwaretechnik, SE 2018, 5.-9. März 2018, Ulm, Germany.)

Debugging Static Analysis - Nguyen Quang Do, Lisa; Krüger, Stefan; Hill, Patrick; Ali, Karim; Bodden, Eric (IEEE Transactions on Software Engineering)
Keywords: Debugging; Static analysis; Tools; Computer bugs; Standards; Writing; Encoding; Testing and Debugging; Program analysis; Development tools; Integrated environments; Graphical environments; Usability testing

Software Engineering und Software Management 2018, Fachtagung des GI-Fachbereichs Softwaretechnik, SE 2018, 5.-9. März 2018, Ulm, Germany

Proceedings of the 27th ACM SIGSOFT International Symposium on Software Testing and Analysis, ISSTA 2018, Amsterdam, The Netherlands, July 16-21, 2018

Model Checking the Information Flow Security of Real-Time Systems - Gerking, Christopher; Schubert, David; Bodden, Eric (Engineering Secure Software and Systems)

Gamifying Static Analysis - Nguyen Quang Do, Lisa; Bodden, Eric (Proceedings of the 2018 26th ACM Joint Meeting on European Software Engineering Conference and Symposium on the Foundations of Software Engineering)
Keywords: Gamification; Integrated Environments; Program analysis

The Secret Sauce in Efficient and Precise Static Analysis: The Beauty of Distributive, Summary-based Static Analyses (and How to Master Them) - Bodden, Eric (ACM SIGPLAN International Workshop on the State Of the Art in Java Program Analysis (SOAP 2018))
Keywords: ATTRACT; ITSECWEBSITE

Towards Ensuring Security by Design in Cyber-Physical Systems Engineering Processes - Geismann, Johannes; Gerking, Christopher; Bodden, Eric (International Conference on Software and System Processes (ICSSP))
Keywords: ITSECWEBSITE

Maschinelle Entscheidungsfindung: Der Einsatz der Fuzzy-Logik in der Rechtswissenschaft - Krimphove, Dieter; Niehaus, Sabastian (Rechtshandbuch Legal Tech)

Self-adaptive Static Analysis - Bodden, Eric (Proceedings of the 40th International Conference on Software Engineering: New Ideas and Emerging Results)
Keywords: ATTRACT; ITSECWEBSITE

VISUFLOW, a Debugging Environment for Static Analyses - Nguyen Quang Do, Lisa; Krüger, Stefan; Hill, Patrick; Ali, Karim; Bodden, Eric (International Conference for Software Engineering (ICSE), Tool Demonstrations Track)
Keywords: ATTRACT; ITSECWEBSITE

Offenzeit plasmaaktivierter Polymeroberflächen für robuste klebtechnische Prozesse (OffPlas) - Aßmuth, Verena; Teutenberg, Dominik; Meschut, Gerson; Stepanov, Sergey; Ihde, Jörg; Mayer, Bernd (18. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Comparison of postural stability in the ACL deficient and reconstructed leg: a Meta analysis - Lehmann, T; Paschen, Linda; Baumeister, Jochen

Negative emotional stimuli increase neurocognitive processing in the brain - An, YW; DiTrani Lobacz, A; Baumeister, Jochen; Swanik, CB

Exploring Functional Brain Connectivity of Postural Control in Upright Stance - Lehmann, T; Büchel, D; Cockcroft, J; Louw, QA; Baumeister, Jochen (Proceedings of the 3rd International Mobile Brain/Body Imaging Conference)

Effect of a cognitive dual-task on electrocortical activation during single leg stance - Büchel, D; Lehmann, T; Cockcroft, J; Louw, QA; Baumeister, Jochen (Proceedings of the 3rd International Mobile Brain/Body Imaging Conference)

Safety Requirements Engineering for Early SIL Tailoring - Fockel, Markus
Der hohe Grad an Innovation in mechatronischen Systemen führt zu sogenannten Cyber-Physical Systems (CPS). Diese haben eine komplexe Funktionalität und Kommunikation. Wie sicherheitskritisch solche Systeme sind, wird durch sogenannte Sicherheits-Integritätslevel (SIL) kategorisiert, die durch Normen wie der ISO 26262 definiert werden. Ein bestimmter SIL beschreibt nicht nur die Höhe des Gefährdungsrisikos, sondern diktiert auch den erforderlichen Grad an Sorgfalt bei der Entwicklung des Systems. Ein hoher SIL erfordert die Anwendung von Safety-Maßnahmen mit einem hohen Sorgfaltsgrad in allen Phasen der Entwicklung und impliziert daher einen hohen Safety-Aufwand. SIL-Tailoring ist ein Mittel um den Safety-Aufwand zu reduzieren, indem man Subsystemen geringere SILs zuordnet, falls sie von kritischeren Subsystemen getrennt sind oder redundante Safety-Anforderungen erfüllen. Um den nötigen Safety-Aufwand zu planen, sollten Möglichkeiten für SIL-Tailoring so früh wie möglich identifiziert werden - d.h. bereits in der Anforderungsanalyse. Durch die Komplexität von CPS, ist es schwierig valide SIL-Tailorings zu finden. Die Validität von SIL-Tailorings muss durch Analyse von Fehlerpropagierungspfaden geprüft und durch Argumente im Safety Case begründet werden. Der Beitrag dieser Dissertation ist ein systematischer, tool-unterstützter SIL-Tailoring-Prozess, der im Safety Requirements Engineering angewendet wird. Der Prozess nutzt eine modell-basierte, formale Anforderungsspezifikation und stellt einen Katalog von Anforderungsmustern bereit. Basierend auf diesen Anforderungen werden Fehlerpropagierungsmodelle generiert und Subsystemen automatisch SILs zugeordnet. Das minimiert den Sicherheitsanalyseaufwand. Aus den generierten Ergebnissen wird automatisch ein Safety Case mit Argumenten für die SIL-Tailoring-Validität abgeleitet.

Threat Analysis in Practice - Systematically Deriving Security Requirements - Fockel, Markus; Merschjohann, Sven; Fazal-Baqaie, Masud (19th International Conference on Product-Focused Software Process Improvement (PROFES 2018))
With the growing number of incidents, the topic security gains more and more attention across all domains. Organizations realize their lack of state-of-the-art security practices, however, they struggle to improve their software lifecycle in terms of security. In this talk, we introduce the concept of security by design that implements security practices within the whole software lifecycle. Based on our practical experience from industry projects in the regulated industrial automation and unregulated classical IT domain, we explain how to perform a threat analysis and how to integrate it into the software lifecycle.

Towards Preserving Information Flow Security on Architectural Composition of Cyber-Physical Systems - Gerking, Christopher; Schubert, David (European Conference on Software Architecture (ECSA 2018))

Model-Driven STEP Application Protocol Extensions Combined with Feature Modeling Considering Geometrical Information - Koch, Thorsten; Holtmann, Jörg; Lindemann, Timo (Revised Selected Papers of the 5th International Conference on Model-Driven Engineering and Software Development)
Original equipment manufacturers (OEMs) build mechatronic, variant-rich systems using components from several suppliers in industry sectors like automation. The OEMs have to integrate the different components to the overall system based on a virtual layout. For this purpose, the suppliers provide geometrical information via the standardized exchange format STEP. Beyond the geometrical information, the OEMs need additional logical and technical information for the integration task as well as the variant handling. For that reason, STEP provides an extension mechanism for extending and tailoring STEP to project-specific needs. However, extending STEP requires extending several capabilities of all involved tools, which prevents the project-specific utilization of the STEP extensions mechanism. In order to cope with this problem, we presented in previous work a model-driven approach enabling the flexible specification of STEP extensions and particularly the automatic derivation of the required capability extensions for two involved tools. Nevertheless, the OEMs still need to apply several engineering tools from different domains to consider logical as well as geometrical constraints between product variants. In this paper, we hence combine our previous approach with extended feature models that consider conventional logical and particularly geometrical information, thereby enabling a holistic product line engineering for mechatronic systems. By means of an automation production system example, we illustrate how OEMs can orchestrate their overall supply and development processes through the combination of both approaches.

Towards Scenario-based Security Requirements Engineering for Cyber-Physical Systems - Koch, Thorsten (International Workshop on Security for and by Model-Driven Engineering (SecureMDE 2018))

Traceable Threat Modeling for Safety-critical Systems - Geismann, Johannes (IEEE International Conference on Software Architecture Companion (ICSA-C 2018))

Automated Synthesis of a Real-Time Scheduling for Cyber-Physical Multi-core Systems - Geismann, Johannes; Höttger, Robert; Krawczyk, Lukas; Pohlmann, Uwe; Schmelter, David (Model-Driven Engineering and Software Development)
Cyber-physical Systems are distributed, embedded systems that interact with their physical environment. Typically, these systems consist of several Electronic Control Units using multiple processing cores for the execution. Many systems are applied in safety-critical contexts and have to fulfill hard real-time requirements. The model-driven engineering paradigm enables system developers to consider all requirements in a systematical manner. In the software design phase, they prove the fulfillment of the requirements using model checking. When deploying the software to the executing platform, one important task is to ensure that the runtime scheduling does not violate the verified requirements by neglecting the model checking assumptions. Current model-driven approaches do not consider the problem of deriving feasible execution schedules for embedded multi-core platforms respecting hard real-time requirements. This paper extends the previous work on providing an approach for a semi-automatic synthesis of behavioral models into a deterministic real-time scheduling. We add an approach for the partitioning and mapping development tasks. This extended approach enables the utilization of parallel resources within a single ECU considering the verification assumptions by extending the open tool platform App4mc. We evaluate our approach using an example of a distributed automotive system with hard real-time requirements specified with the MechatronicUML method.

Formal, Model- and Scenario-based Requirement Patterns - Fockel, Markus; Holtmann, Jörg; Koch, Thorsten; Schmelter, David (6th International Conference on Model-Driven Engineering and Software Development (MODELSWARD 2018))
Distributed, software-intensive systems such as automotive electronic control units have to handle various situations employing message-based coordination. The growing complexity of such systems results in an increasing difficulty to achieve a high quality of the systems' requirements specifications. Scenario-based requirements engineering addresses the message-based coordination of such systems and enables, if underpinned with formal modeling languages, automatic analyses for ensuring the quality of requirements specifications. However, formal requirements modeling languages require high expertise of the requirements engineers and many manual iterations until specifications reach high quality. Patterns provide a constructive means for assembling high-quality solutions by applying reusable and established building blocks. Thus, they also gained momentum in requirements documentation. In order to support the requirements engineers in the systematic conception of formal, scenario-based requirements specification models, we hence introduce in this paper a requirement pattern catalog for a requirements modeling language. We illustrate and discuss the application of the requirement patterns with an example of requirements for an automotive electronic control unit.

Improving Quality Control of Mechatronic Systems Using KPI-Based Statistical Process Control - Wohlers, Benedict; Dziwok, Stefan; Schmelter, David; Lorenz, Wadim (Advances in Manufacturing, Production Management and Process Control - AHFE 2018)

Model-driven allocation engineering: specifying and solving constraints based on the example of automotive systems - Pohlmann, Uwe; Hüwe, Marcus (Automated Software Engineering)
Automotive systems provide sophisticated functionality and are controlled by networked electronic control units (ECUs). Nowadays, software engineers use component-based development approaches to develop their software. Moreover, software components have to be allocated to ECUs to be executed. Engineers have to cope with topology-, software-, and timing dependencies and memory-, scheduling-, and routing constraints. Currently, engineers use linear programming to specify allocation constraints manually and to compute a feasible allocation specification automatically. However, encoding the allocation problem as a linear program is a complex and error-prone task. This paper contributes a model-driven, object constraint language based, and graph pattern based allocation engineering approach for reducing the engineering effort and to avoid failures. We validate our approach with an automotive case study. We specify the software component model, the hardware platform model, and the allocation constraint specification with our engineering approach MechatronicUML. Our validation shows that we can specify allocation constraints with less engineering effort and are able to compute feasible allocation specifications automatically.

A Model-driven Software Construction Approach for Cyber-physical Systems - Pohlmann, Uwe

Inverse Optimal Control : theoretical study - Maslovskaya, Sofya

Kritische Entgegnung auf die Studie "Zur Relevanz informatischer Bildung in der Schule für den Erwerb computer- bzw. informationsbezogener Kompetenzen" - Brinda, Torsten; Diethelm, Ira; Hellmig, Lutz; Magenheim, Johannes; Romeike, Ralf; Schroeder, Ulrik (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)

Synergies Take Center Stage - Sievers, Sönke; Keienburg, Georg; Schmid, Timo; Degen, Dominik

Blog post by Prof. Sönke Sievers: Kapitalmarktorientierte Erfolgsmessung von M&A Transaktionen – Deutsche und weltweite Evidenz. - Sievers, Sönke

Update on the M&A market entitled As Prices Peak, Should Dealmakers wait for the next Downturn? - Sievers, Sönke; Degen, Dominik; Keienburg, Georg; Schmid, Timo; Kengelbach, Jens

Post on Paying for Performance in Private Equity: Evidence from VC Partnerships. - Sievers, Sönke; Robinson, David T.; Hüther, Niklas; Hartmann-Wendels, Thomas

On the runtime of universal coating for programmable matter - J. Daymude, Joshua; Derakhshandeh, Zahra; Gmyr, Robert; Porter, Alexandra; W. Richa, Andrea; Scheideler, Christian; Strothmann, Thim Frederik (Natural Computing)

Heterogenität als Chance. Bilanz und Perspektiven des Qualitätspakt Lehre-Projektes an der Universität Paderborn

Digitale Medien im Maßregelvollzug. Qualifizierungskonzept zum Mediencoach & Praxisleitfaden für die medienpädagogische Arbeit mit Patientinnen und Patienten. Schwerpunkt: Digitale Foto- und Videoarbeit

Hochschulstrategie als Prozess. Zum allgemeinen und hochschulspezifischen Begriff der Strategie - Graf-Schlattmann, Marcel; Meister, Dorothee M.; Oevel, Gudrun; Wilde, Melanie

Monotone Suchbarkeit bei den selbststabilisierenden Protokollen Build-List und Build-Multilist mit systemverlassenden Knoten - N., N.

Gathering Strategien für mobile Roboterschwärme im Gitternetz - N., N.

Decontaminating Planar Regions with Finite Automaton Robots and Tiles - N., N.

Load-Balanced Routing in Hybriden Kommunikationsnetzwerken - Wulfes, Robin

Ein Futurelab für die Medienpädagogik - Knaus, T.; Meister, Dorothee M.; Narr, K. (Futurelab Medienpädagogik. Qualitätsentwicklung. Professionalisierung. Standards. Schriften zur Medienpädagogik 54)

Qualitätsentwicklung – Professionalisierung – Standards. Thesen aus medienpädagogischer Sicht - Knaus, T.; Meister, Dorothee M.; Tulodziecki, G. (Futurelab Medienpädagogik. Qualitätsentwicklung. Professionalisierung. Standards. Schriften zur Medienpädagogik 54)

Digitalisierung erfordert professionelle medienpädagogische Unterstützung - Knaus, T.; Meister, Dorothee M.; Narr, K. (Futurelab Medienpädagogik. Qualitätsentwicklung. Professionalisierung. Standards. Schriften zur Medienpädagogik 54)

Quality Development – Professionalization – Standards. A Mediapedagogy Futurelab - Knaus, T.; Meister, Dorothee M.; Tulodziecki, G. (Futurelab Medienpädagogik. Qualitätsentwicklung. Professionalisierung. Standards. Schriften zur Medienpädagogik 54)

Medienpädagogik in pädagogischen Grenzfeldern – konzeptionelle Überlegungen am Beispiel des Maßregelvollzugs - Kamin, A.-M.; Meister, Dorothee M.; Sonnenschein, N. (Spannung? Potentiale! – Spannungsfelder des Digitalen und Bildungspotentiale)

Performance of Mask Based Statistical Beamforming in a Smart Home Scenario - Heymann, Jahn; Bacchiani, M.; Sainath, T. N. (2018 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Exact formulation of the transverse dynamic spin susceptibility as an initial-value problem - Schindlmayr, Arno (Advances in Mathematical Physics)
The transverse dynamic spin susceptibility is a correlation function that yields exact information about spin excitations in systems with a collinear magnetic ground state, including collective spin-wave modes. In an ab initio context, it may be calculated within many-body perturbation theory or time-dependent density-functional theory, but the quantitative accuracy is currently limited by the available functionals for exchange and correlation in dynamically evolving systems. To circumvent this limitation, the spin susceptibility is here alternatively formulated as the solution of an initial-value problem. In this way, the challenge of accurately describing exchange and correlation in many-electron systems is shifted to the stationary initial state, which is much better understood. The proposed scheme further requires the choice of an auxiliary basis set, which determines the speed of convergence but always allows systematic convergence in practical implementations.

Additive Fertigung in der modernen Orthopädietechnik - Anwendung und Forschungsansätze - - Schafran, T.; Schramm, B.; Risse, L. (DVM - AK Implantate und Biostrukturen)

Additive manufacturing for medical applications - Schramm, B.; Risse, L.; Brüggemann, J.P.; Richard, H.A.; Kullmer, G. (Journal of 3D Printing in medicine)

Welche ingenieurstechnischen Perspektiven bietet die Versorgung durch additiv gefertigte Orthesen? - Risse, L.; Schramm, B.; Schafran, T. (PreDay AK Fußchirurgie)

The Influence of Contour Scanning Parameters and Strategy on Selective Laser Sintering PA613 Build Part Properties - Kummert, C.; Schmid, H.-J. (29th Annual International Solid Freeform Fabrication Symposium)

Validierung der strukturmechanischen Funktionsfähigkeit durch experimentelle Bauteilprüfungen additiv gefertigter Leichtbaustrukturen - Brüggemann, J.P.; Risse, L.; Grübel, A.; Richard, H.A.; Kullmer, G. (DVM - Bericht 250, Arbeitskreis: Bruchmechanische Werkstoff- und Bauteilbewertung: Beanspruchungsanalyse, Prüfmethoden und Anwendungen, Deutscher Verband für Materialforschung und -prüfung e.V.)

Entwicklung und Umsetzung eines Qualitätssicherungskonzeptes für die additive Fertigung - Dsuban, A.; Lohn, J.; Brüggemann, J.P.; Kullmer, G. (DVM - Bericht 403, Arbeitskreis: Additiv gefertigte Bauteile und Strukturen, Deutscher Verband für Materialforschung und -prüfung e.V.)
although it shows great potential. In this paper, first approaches

Entwicklung von Optimierungsstrategien unter Ausnutzung des Potentials der additiven Fer-tigung - Brüggemann, J.P.; Risse, L.; Richard, H.A.; Kullmer, G. (DVM - Bericht 403, Arbeitskreis: Additiv gefertigte Bauteile und Strukturen, Deutscher Verband für Materialforschung und -prüfung e.V.)

CAE-gestützte Optimierung eines Hüftimplantats durch Ausnutzung der Potentiale additiver Fertigungsverfahren - Risse, L.; Schramm, B.; Brüggemann, J.P.; Woodcock, S.C.; Kullmer, G.; Richard, H.A. (DVM-Bericht 403, Arbeitskreis: Additiv gefertigte Bauteile und Strukturen, Deutscher Verband für Materialforschung und -prüfung e.V.)

Crack Growth Simulation with Adapcrack3D in 3D Structures under the influence of Temperature - Joy, T.D.; Brüggemann, J.P.; Kullmer, G. (Procedia Structural Integrity)
results clearly demonstrate the great potential of additive

Optimization of the fracture mechanical properties of additively manufactured EN AW-7075 - Brüggemann, J.P.; Risse, L.; Kullmer, G.; Schramm, B.; Richard, H.A. (Procedia Structural Integrity)

Fracture mechanical investigations on selective laser melted TiAl6V4 - Brüggemann, J.P.; Risse, L.; Kullmer, G.; Richard, H.A. (Procedia Structural Integrity)

Entwicklung von steifigkeitsangepassten, lasergeschmolzenen Kurzschaft-Hüftendoprothesen - Risse, L.; Schramm, B.; Brüggemann, J.P.; Kullmer, G.; Richard, H.A. (Proceedings of the 15th Rapid.Tech Conference)

Topology Optimized Heat Transfer Using the Example of an Electronic Housing - Menge, Dennis; Delfs, Patrick; Töws, Marcel; Schmid, Hans-Joachim (29th Annual International Solid Freeform Fabrication Symposium)
Function integration is a key issue for an efficient and economic usage of Additive Manufacturing. An efficient heat transfer by topology optimized structures is a rarely considered approach which will be outlined with an exemplary electronic housing which has been newly designed. A commercial projector unit, whose electrical components in total produce 38 W, shall be integrated in the closed housing and passively cooled by natural convection. Topology optimized structures shall be generated in the inner part of the housing to transfer the heat homogenously from the projector components to the housing wall while simultaneously minimizing the mass. At the outside of the housing walls, lattice and rib structures are applied to increase the effective surface for heat transfer by natural convection and radiation. Furthermore, the housing geometry is optimized regarding a minimization of support structures to reduce the post-processing effort. Finally, the housing shall be built of AlSi10Mg by SLM.

Thermoplastic Elastomer Part Color as Function of Temperature Histories and Oxygen Atmosphere During Selective Laser Sinterung - Kummert, Christina; Josupeit, Stefan; Schmid, Hans-Joachim (Journal of Minerals, Metals and Materials Society)
The influence of selective laser sintering (SLS) parameters on PA12 part properties is well known, but research on other materials is rare. One alternative material is a thermoplastic elastomer (TPE) called PrimePart ST that is more elastic and shows a distinct SLS processing behavior. It undergoes a three-dimensional temperature distribution during the SLS process within the TPE part cake. To examine this further, a temperature measurement system that allows temperature measurements inside the part cake is applied to TPE in the present work. Position-dependent temperature histories are directly correlated with the color and mechanical properties of built parts and are in very good agreement with artificial heat treatment in a furnace. Furthermore, it is clearly shown that the yellowish discoloration of parts in different intensities is not only temperature dependent but also influenced by the residual oxygen content in the process atmosphere. Nevertheless, the discoloration has no influence on the mechanical part properties.

A Novel Approach to the Modelling of Transport Phenomena in Random Packings - Salten, Alexander Heinrich Johannes; Maćkowiak, Jan; Maćkowiak, Jerzy; Kenig, Eugeny (Chemical Engineering Transactions)

A novel approach for the determination of transport phenomena in random packings - Salten, Alexander Heinrich Johannes; Maćkowiak, J. F.; Maćkowiak, J.; Kenig, Eugeny
Keywords: PubList

A novel approach to the modelling of transport phenomena in random packings - Salten, Alexander Heinrich Johannes; Maćkowiak, J. F.; Maćkowiak, J.; Kenig, Eugeny
Keywords: PubList

Additive Manufacturing of a Soft Magnetic Rotor Active Part and Shaft for a Permanent Magnet Synchronous Machine - Urbanek, Stefan; Ponick, Bernd; Taube, Alexander; Hoyer, Kay-Peter; Schaper, Mirko; Lammers, Stefan; Lieneke, Tobias; Zimmer, Detmar (Conference paper, 2018 IEEE Transportation Electrification Conference and Expo (ITEC), Juni 2018, DOI: 10.1109/ITEC.2018.8450250)

Software-assisted design check of additive manufactured components - Tominski, Johannes; Lammers, Stefan (14th PERMAS Users' Conference)

Method for a Software-based Design Check of Additively Manufactured Components - Tominski, Johannes; Lammers, Stefan; Wulf, Christian; Zimmer, Detmar (29th Annual International Solid Freeform Fabrication Symposium)
This paper reports on the experimental development and the theoretical analysis of the scanning laser epitaxy (SLE) process that is currently being investigated and developed at the Georgia Institute of Technology. SLE is a laser-based manufacturing process for deposition of equiaxed, directionally solidified and single-crystal nickel superalloys onto superalloy substrates through the selective melting and re-solidification of superalloy powders. The thermal modeling of the system, done in a commercial CFD software package, simulates a heat source moving over a powder bed and considers the approximate change in the property values for consolidating CMSX-4 nickel superalloy powder. The theoretical melt depth is obtained from the melting temperature criteria and the resulting plots are presented alongside matching experimental micrographs obtained through cross-sectional metallography. The influence of the processing parameters on the microstructural evolution, as evidenced through observations made from the micrographs, is discussed. This work is sponsored by the Office of Naval Research, through grants N00173-07-1-G031 and N00014-10-1-0526.

Ein Beitrag zur Anpassung bestehender Konstruktionsmethodiken an die additiven Fertigungsverfahren - Künneke, Thomas; Bücker, Sonja; Lieneke, Tobias; Zimmer, Detmar (Proceedings of the 15th Rapid.Tech Conference)
In der Industrie entsteht aufgrund des dynamischen Wettbewerbsumfelds ein zunehmender Drang nach verkürzten Produktentstehungszeiten, hoher Funktionsintegration und individualisierten Produkten. Mithin erlangen additive Fertigungsverfahren eine zunehmende industrielle Bedeutung. Das Laser-Strahlschmelzen (LBM) als additives Verfahren ist hierbei beispielhaft hervorzuheben, da es bereits im Bereich des Prototypenbaus und der Kleinserienfertigung ein etabliertes Verfahren ist, das an der Schwelle zum Einsatz in der Serienproduktion steht. Entscheidendes Hemmnis für den Einsatz der additiven Fertigungsverfahren bildet die fehlende methodische Ausnutzung der gestalterischen Freiheiten und Randbedingungen durch die vergleichsweise neuartige Gruppe an Fertigungsverfahren im gesamten Produktentstehungsprozess. In der Produktentwicklung bildet die Konstruktionsmethodik einen möglichen Ansatz, um gestalterische Freiheiten und Vorteile additiver Fertigungsverfahren bereits in frühen Phasen der Entwicklung gezielt zu berücksichtigen. Hierfür werden aufgrund bestehender und allgemein anerkannter Konstruktionsmethoden (z.B. VDI2221, Pahl/Beitz, etc.) Anknüpfungspunkte aufgezeigt, die eine Implementierung, speziell des Laser-Strahlschmelzens, ermöglichen. Besonderes Augenmerk wird in dieser Veröffentlichung auf die beiden Konstruktionsphasen Konzeption und Gestaltung gelegt. Hierzu werden Ergänzungen oder Anpassungen der bestehenden Konstruktionsmethoden vorgestellt. In besonderer Weise wird dabei auf die Einbringung und die Vorteile der additiven Fertigungsverfahren eingegangen.

Iterative Produktentwicklung und Produktionsplanung für die Additive Fertigung - Jacob, Alexander; Künneke, Thomas; Lieneke, Tobias; Baumann, Tobias; Stricker, Nicole; Zimmer, Detmar; Lanza, Gisela (ZWF Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Die Additive Fertigung eröffnet neue Freiheitsgrade in der Produktentwicklung. Unsicherheiten über die Wirtschaftlichkeit und Leistungsfähigkeit der aus der Konstruktion ableitbaren Fertigungstechnologieketten sind zu beachten. In diesem Beitrag wird eine Methode vorgestellt, welche die Anpassung einer bestehenden Konstruktionsmethode berücksichtigt und eine iterative Bewertung der Konstruktionsentscheidungen anhand von Technologieketten ermöglicht. Hiermit können die Potenziale der additiven Fertigungstechnologien zielgerichtet realisiert werden.

Thin liquid droplet on top of a rotating non-isothermal liquid layer - Boettcher, Konrad; Bothe, Mike (PAMM)

Section I: Digital Humanities: The Role of the Digital in English Philology - Bartsch, Sabine; Mindt, Ilka (Anglistentag 2017 Regensburg. Proceedings)

Englischer Sprachwandel im Zeitalter von Digitalisierung und Innovation - Mindt, Ilka

Entwurf und simulationsgestützte Analyse eines mechanisch rekonfigurierbaren Mehrmotorengetriebes - Brückner, Uwe

Entwurf einer intelligenten Betriebsstrategie für Mehrmotorenantriebssysteme und ihre Anwendung auf Kautschukinnenmischer - Strop, Malte

Elektromechanische Antriebe - Brückner, Uwe; Künneke, Thomas; Schadomsky, Magnus Hubert; Strop, Malte; Zimmer, Detmar

Dynamics of DNA Origami Lattice Formation at Solid–Liquid Interfaces - Kielar, Charlotte; Ramakrishnan, Saminathan; Fricke, Sebastian; Grundmeier, Guido; Keller, Adrian (ACS Applied Materials & Interfaces)

Structural stability of DNA origami nanostructures under application-specific conditions - Ramakrishnan, Saminathan; Ijäs, Heini; Linko, Veikko; Keller, Adrian (Computational and Structural Biotechnology Journal)

Pharmacophore Nanoarrays on DNA Origami Substrates as a Single-Molecule Assay for Fragment-Based Drug Discovery - Kielar, Charlotte; Reddavide, Francesco V.; Tubbenhauer, Stefan; Cui, Meiying; Xu, Xiaodan; Grundmeier, Guido; Zhang, Yixin; Keller, Adrian (Angewandte Chemie International Edition)

Superstructure-Dependent Loading of DNA Origami Nanostructures with a Groove-Binding Drug - Kollmann, Fabian; Ramakrishnan, Saminathan; Shen, Boxuan; Grundmeier, Guido; Kostiainen, Mauri A.; Linko, Veikko; Keller, Adrian (ACS Omega)

Directed Protein Adsorption Through DNA Origami Masks - Ramakrishnan, Saminathan; Grundmeier, Guido; Keller, Adrian (DNA Nanotechnology: Methods and Protocols)

On the Stability of DNA Origami Nanostructures in Low-Magnesium Buffers - Kielar, Charlotte; Xin, Yang; Shen, Boxuan; Kostiainen, Mauri A.; Grundmeier, Guido; Linko, Veikko; Keller, Adrian (Angewandte Chemie International Edition)

On the Adsorption of DNA Origami Nanostructures in Nanohole Arrays - Brassat, Katharina; Ramakrishnan, Saminathan; Bürger, Julius; Hanke, Marcel; Doostdar, Mahnaz; Lindner, Jörg; Grundmeier, Guido; Keller, Adrian (Langmuir)

Ultrasound-mediated deposition and cytocompatibility of apatite-like coatings on magnesium alloys - Liu, Chen-Ni; Böke, Frederik; Gebhard, Maximilian; Devi, Anjana; Fischer, Horst; Keller, Adrian; Grundmeier, Guido (Surface and Coatings Technology)

Adsorption and Fibrillization of Islet Amyloid Polypeptide at Self-Assembled Monolayers Studied by QCM-D, AFM, and PM-IRRAS - Hajiraissi, Roozbeh; Hanke, Marcel; Yang, Yu; Duderija, Belma; Gonzalez Orive, Alejandro; Grundmeier, Guido; Keller, Adrian (Langmuir)

Business Model Portfolio Planning for Smart Services - Koldewey, Christian; Echterfeld, Julian; Reilender, Meikel; Gausemeier, Jürgen (Proceedings of the ISPIM connects)